United States. Dept. of State memorandum and illustrations - United States. Department of State
Memorandum stipulating the appropriate costume for members of the American diplomatic mission to Ghent and drawings of clothing and of a pattern for embroidery.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Costume -- History -- United States -- 19th century; Diplomatic and consular service, American -- Belgium; Embroidery; Ghent (Belgium) -- Social life and customs